O direito à educação: um estudo sobre as políticas de educação especial no Brasil (1974/2008) - Goes, Ricardo Schers de (2009)
This master dissertation aims to analyze, through the propositions of the federal policies in Brazil within the period from 1974 to 2008, how the right to education of a percentage of the population that have been focused by sectorial policies was created, namely, the polices of special education. The delimitation of the initial year for data collecting was chosen due to the creation of the National Center for Special Education CENESP, in 1974, the first federal organ with specific attributions in the area of special education. The year 2008 was chosen because it was the year that the last policy proposition in this area was published in the federal field. The data resources in this research were, fundamentally, three base-documents produced in this period that tried to define the principles that guide these policies: 1) Guidelines and Bases for Action of the National Center for Special Education (BRASIL. MEC. CENESP, 1974); 2) National Policy on Special Education (BRASIL. MEC. SEESP, 1994); and 3) National Policy on Special Education from the Perspective of Inclusive Education (BRASIL. MEC. SEESP, 2008). Subsidiary documents were used when necessary because they are either more specific than these policy propositions of large scope or they are more comprehensive legislations and documentation (guidelines and bases law, federal constitution or worldwide declarations). The analysis of these documents offered us the following main results: the undefined field in which the special education acts contributes to the maintenance of sectorial policies about problems that are in the field of global educational policies; the universalization of the access to basic school (one of the expressions of the right to education) is far from the point to be reached in relation to the students included by the special education; and the permanence and valorization of private institutions with philanthropic character, that assume relevant role in the policy and in the educational attendance of this population, contributes to the maintenance of the disabled people schooling in the field of moral commitment and not in the field of the rights